Isolamento, identificação e suscetibilidade in vitro de leveduras isoladas da cavidade oral de fêmeas caninas - Santin, Rosema (2009)
The aims of this study was the oral cavity evaluation of females stray dogs from Pelotas-RS, as well as yeast isolation and identification from three different areas of this cavity, comparison of two technique of sample collection (swabs and curettes) and test the in vitro susceptibility of isolated yeasts against common oral antiseptics used in pets. Fifty-nine randomized animals were included in the study. All of them were SRD, without age defined and from Pelotas-RS. They were divided in three groups of ages by the evaluation of dental arc, and were examined to determine the cranial morphology, presence of dental plaque, tooth fractures, malocclusion, halitosis and gingival bleeding. Measure of periodontal groove depth was also done. Samples were collected from three areas, gingival mucosa, dental biofilm and periodontal grooves, with different collection techniques: swab, curettes, millimeter periodontal probe and cellulose polymers membranes. In vitro susceptibility tests by microdilution methods was done with 15 of those yeasts against A product (0,12% chlorhexidine gluconate, 0,12% benzalkonium chloride and 0,10% chlorophila extract) and B product (0,2% benzalkonium chloride, 1% propolis and 0,5% peppermint arome). It was also evaluated chemical principles of products in separated, as chlorhexidine gluconate, benzalkonium chloride and propolis. Tooth fractures was observed in higher proportion at animals with six or more years old (p=0,0030). Dogs younger than 2 years old had lower rate of dental plaques than the others groups (p=0,0000). The association of positive areas of yeast isolation with age, tooth fracture, dental plaque, halitosis, gingival bleeding or malocclusion was not statistically significant. Sixty-one yeasts were isolated, characterized by M. pachydermatis (50,82%), Rhodotorula spp. (13,11%), C. albicans (4,92%), C. catenulata (3,28%), C. famata (1,64%), C. guilliermondii (1,64%), C. parapsilosis (1,64%), C. intermedia (1,64%), T. asahii (13,11%), T. mucoide (1,64%) and C. albidus (6,56%), from 30 (50,85%) animals. Yeasts growing inhibition was observed in all products tested and in all concentrations of them, with exception of propolis that did not show activity against yeasts. In conclusion, at oral cavity exam of female dogs, the mainly alterations found were dental plaques, tooth fractures and malocclusion. Isolated yeasts are normal habitants from the three different areas of oral cavity studied, without resulting in clinical signs. In relation to the techniques, it was not found difference between swab and curettes for oral sample collection. Yeast isolation was higher in female dogs that show halitosis. Oral antiseptics tested, as well as chlorhexidine gluconate and benzalkonium chloride were effective against yeasts isolated from canine oral cavity in all dilution tested. Propolis, at the conditions and dilutions tested, is not recommended as an oral antiseptic against yeast.